Biochemical and Microbiological Quality of Ice Stored Catfish Wallago attu of the Imphal Market - W., Vishwanath; H., Lilabati (Fishery Technology, 2025)
The biochemical and microbiological quality of ice stored Wallago attu sold in the Imphal market of Manipur, India were studied. TVBN and FFA values were high at 12.00Â±1.73 mg lOOg"1 and 5.50Â±0.29% oleic acid, respectively. TBA value was 0.73 mg of malondaldehyde kg"1 of sample. Salmonella and Escherichia coli were not detected. However, presence of Staphylococcus aureus, faecal Streptococci, coliforms and a high content of bacteria (108 g"1) and fungi (103 g"1) indicated that the fishes were probably from polluted waters and/or proper sanitary care was not taken after capture. Presence of psychrophiles viz., Pseudomonas and Flavobacterium in great numbers indicated probability of the incidence of spoilage in the fish.